2021
DOI: 10.3390/diseases9030064
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin as an Add-On Treatment of COVID-19 Infection: Current Status

Abstract: This brief review was written to provide a perspective on the flurry of reports suggesting that melatonin can be an important add-on therapy for COVID-19. Despite the passage of more than 60 years since its discovery and much evidence representing the contrary, there has been great reluctance to conceive melatonin as anything other than a hormone. Many other body chemicals are known to have multiple roles. Melatonin was first shown to be a hormone derived from the pineal gland, to be actively synthesized there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 48 publications
(51 reference statements)
0
9
0
Order By: Relevance
“…A delay from diagnosis to treatment has been shown to minimize any positive effect of treatment. 8,16,17 Nevertheless, the concept of this study is generalizable because many patients do not present for evaluation on the first day of symptoms and there may be a lag time while accessing and awaiting laboratory test results. The strengths of this study include accessibility of our surveys, in English and Spanish, and to those isolated in their homes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A delay from diagnosis to treatment has been shown to minimize any positive effect of treatment. 8,16,17 Nevertheless, the concept of this study is generalizable because many patients do not present for evaluation on the first day of symptoms and there may be a lag time while accessing and awaiting laboratory test results. The strengths of this study include accessibility of our surveys, in English and Spanish, and to those isolated in their homes.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin C (ascorbic acid) and melatonin (N-acetyl-5-methoxytryptamine) have been suggested as potential therapies to protect against the acute lung injury and other sequelae characteristic of COVID-19 infection. [2][3][4] These antioxidizing agents may disrupt the cytokine cascade to prevent further end organ damage in the setting of acute infection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 6 , 7 Although it is primarily synthesized in the pineal gland, but other organs of the body, including the brain, lymphocytes, skin, the gastrointestinal tract, thymus, eye and bone marrow also contribute to its synthesis. 8 It has been recently reported that melatonin specifically targets mitochondria of all cells, as it is mainly synthesized here. 9 It is also known that mitochondria is the main organelle involved in the initiation of intrinsic pathway of apoptosis.…”
Section: Introductionmentioning
confidence: 89%
“…A possible role in protecting pulmonary endothelial cells can be also hypothesized, as observed in pre-eclampsia [ 273 ]. Several authors have proposed melatonin as a useful therapeutic tool in contrasting neurological complications and super-infections for both COVID-19 and PACS patients [ 274 , 275 , 276 , 277 , 278 ], and a significant vantage in mortality and recovery rate has been observed in severe cases [ 279 , 280 , 281 ]. Validation of the therapeutic role of melatonin and its metabolites in COVID-19 and PACS is needed, and clinical trials and the use of reliable animal models are warranted [ 282 , 283 , 284 , 285 , 286 , 287 ].…”
Section: Introductionmentioning
confidence: 99%